(Co)digestão anaeróbia de microalgas em função do pré-tratamento e inóculo - GABRIEL MAGALHÃES CHIQUITO (2024)
With the increase in world population, the demand for food is also growing, and given that a large portion of nutrient reserves for food cultivation are non-renewable, it is imperative to find ways to reuse these resources. Post-treatment of sewage with microalgae in wastewater treatment plants enables the assimilation of a significant portion of the nutrients that would otherwise be discarded into water bodies, causing issues such as eutrophication, and generates a nitrogen-rich biomass with great potential for use as fertilizer in agriculture. Anaerobic digestion is an efficient technology to degrade this algal biomass without causing the loss of assimilated nutrients in the process, also offering the possibility of obtaining other value-added products, such as methane. However, microalgae are a substrate difficult to degrade by the microorganisms responsible for anaerobic digestion, so strategies to optimize this process are necessary to make it more effective and viable. One way to reduce this digestion problem is by pre-treating the substrate to break down the rigid cell wall of microalgae. One of the most commonly used pre-treatments is thermal pre-treatment. Another way to optimize this process is by using co-substrates in digestion that can improve parameters, such as the carbon/nitrogen ratio (C/N ratio), which should be between 20:1 and 30:1 (RAJLAKSHMI et al., 2023). Batch tests were conducted to determine the best conditions for thermal pre-treatment time, inoculum concentration, and co-digestion ratio. It was found that the best option for the anaerobic digestion process was co-digestion, which increased methane yield by 100% and 74% between conditions without and with pre-treatment, respectively, with 1.5 gSV/L of inoculum, while the production rate increased by 124% and 102% for conditions without and with pre-treatment, respectively, with 1gSV/L of inoculum, and by 44% and 64% for conditions without and with pre-treatment, respectively, with 1.5 gSV/L of inoculum. As a final product, a digestate with a low C/N ratio and rich in nitrogen was generated.